A REVIEW OF DRAG REDUCTION BY RIBLETS AND MICRO-TEXTURES IN THE TURBULENT BOUNDARY LAYERS - Samira Sayad Saravi; Kai Cheng (European Scientific Journal, ESJ, 2013)
Drag reduction in wall-bounded flows can be achieved by the passive flow control technique, riblets. In this article, possible physical mechanisms responsible for turbulent drag reduction have been summarized. The modeling and experiments concerning the relationship between the riblets features and the turbulent boundary layer structure has also been reviewed.